Evolution of Superinfection Immunity in Cluster A Mycobacteriophages - Travis N. Mavrich; Graham F. Hatfull (mBio, 2019)
ABSTRACT Temperate phages encode an immunity system to control lytic gene expression during lysogeny. This gene regulatory circuit consists of multiple interacting genetic elements, and although it is essential for controlling phage growth, it is subject to conflicting evolutionary pressures. During superinfection of a lysogen, the prophage’s circuit interacts with the superinfecting phage’s circuit and prevents lytic growth if the two circuits are closely related. The circuitry is advantageous since it provides the prophage with a defense mechanism, but the circuitry is also disadvantageous since it limits the phage’s host range during superinfection. Evolutionarily related phages have divergent, orthogonal immunity systems that no longer interact and are heteroimmune, but we do not understand how immunity systems evolve new specificities. Here, we use a group of Cluster A mycobacteriophages that exhibit a spectrum of genetic diversity to examine how immunity system evolution impacts superinfection immunity. We show that phages with mesotypic (i.e., genetically related but distinct) immunity systems exhibit asymmetric and incomplete superinfection phenotypes. They form complex immunity networks instead of well-defined immunity groups, and mutations conferring escape (i.e., virulence) from homotypic or mesotypic immunity have various escape specificities. Thus, virulence and the evolution of new immune specificities are shaped by interactions with homotypic and mesotypic immunity systems. IMPORTANCE Many aspects regarding superinfection, immunity, virulence, and the evolution of immune specificities are poorly understood due to the lack of large collections of isolated and sequenced phages with a spectrum of genetic diversity. Using a genetically diverse collection of Cluster A phages, we show that the classical and relatively straightforward patterns of homoimmunity, heteroimmunity, and virulence result from interactions between homotypic and heterotypic phages at the extreme edges of an evolutionary continuum of immune specificities. Genetic interactions between mesotypic phages result in more complex mesoimmunity phenotypes and virulence profiles. These results highlight that the evolution of immune specificities can be shaped by homotypic and mesotypic interactions and may be more dynamic than previously considered.